Prognostic value of texture analysis of the primary tumour in high‐risk neuroblastoma: An 18F‐DOPA PET study. Issue 11 (3rd August 2022) - Fiz, Francesco; Bottoni, Gianluca; Bini, Fabiano; Cerroni, Francesca; Marinozzi, Franco; Conte, Massimo; Treglia, Giorgio; Morana, Giovanni; Sorrentino, Stefania; Garaventa, Alberto; Siri, Giacomo; Piccardo, Arnoldo
Abstract: Purpose: To evaluate the prognostic value of texture analysis of the primary tumour with 18 fluorine‐dihydroxyphenylalanine positron emission tomography/X‐ray computed tomography ( 18 F‐DOPA PET/CT) in patients affected by high‐risk neuroblastoma (HR‐NBL). Methods: We retrospectively analysed 18 patients with HR‐NBL, which had been prospectively enrolled in the course of a previous trial investigating the diagnostic role of 18 F‐DOPA PET/CT at the time of the first onset. Texture analysis of the primary tumour was carried out on the PET images using LifeX. Conventional indices, histogram parameters, grey level co‐occurrence (GLCM), run‐length (GLRLM), neighbouring difference (NGLDM) and zone‐length (GLZLM) matrices parameter were extracted; their values were compared with the overall metastatic load, expressed by means of whole‐body metabolic burden (WBMB) score and the progression‐free/overall survival (PFS and OS). Results: There was a direct correlation between WBMB and radiomics parameter describing uptake intensity (SUVmean : p = .004) and voxel heterogeneity (entropy: p = .026; GLCM_Contrast: p = .001). Conversely, texture indices of homogeneity showed an inverse correlation with WBMB (energy: p = .026; GLCM_Homogeneity: p = .006). On the multivariate model, WBMB ( p < .01) and the first standardised uptake value (SUV) quartile ( p < .001) predicted PFS; OS was predicted by WBMB and the N‐myc proto‐oncogene protein (MYCN) amplification ( p < .05) for both. Conclusions: Textural parameters describing heterogeneity and metabolic intensity of the primary HR‐NBL are closely associated with its overall metastatic burden. In turn, the whole‐body tumour load appears to be one of the most relevant predictors of progression‐free and overall survival.